Keterampilan berbahasa: keterampilan menyimak, berbicara, membaca, dan menulis - Ma’la, Amril (Maliki Interdisciplinary Journal, 2025)
Language skills are fundamental abilities required for effective communication in various contexts. This study discusses the importance of four main aspects in language learning: listening, speaking, reading, and writing. Each aspect is interrelated and supports overall language mastery. In language learning, there are stages to be followed, starting from listening to writing, with various methods that can be applied to enhance these skills, such as project-based learning and collaborative approaches. However, several factors influence language proficiency, including limited vocabulary, low motivation, and environmental support. The importance of language skills not only affects an individual’s ability to communicate but also contributes to the development of soft skills and social adaptation. Therefore, systematic efforts are needed to improve language skills through effective teaching methods and adequate support.